Equity of Carbon Pricing Policies in Mitigating Climate Change: A Comparative Study of Different Policy Designs - Kesor, Chhoub (Journal of Public Representative and Society Provision, 2022)
The study aims to evaluate the efficiency and fairness of different carbon pricing policy designs in mitigating climate change. A quantitative methodology is used, analyzing data from several countries and regions that have implemented carbon pricing policies like carbon taxes and cap-and-trade systems. The study utilizes regression analyses to assess the relationship between carbon pricing and greenhouse gas emissions, and statistical analysis to evaluate the distributional effects across different income groups and regions. The study finds that carbon pricing policies are effective in reducing greenhouse gas emissions, but their impact on household income distribution varies. Policies that include revenue recycling methods, such as rebates or investments in renewable energy, are more effective in reducing the regressive impacts on low-income households. The research indicates that careful design of carbon pricing policies is essential to ensure both effectiveness in reducing emissions and fairness in economic impact.